UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Darman (UNISAN JURNAL, 2024)
This study aims to describe and analyze how the professionalism and performance of PAI teachers at Madrasah Aliyah Nurul Islam Jati Agung, South Lampung and how the efforts are made to improve student achievement. This research is a qualitative field research and uses a descriptive analytical approach. The data was collected by means of observation, interviews, and documentation. Data analysis was carried out by giving meaning to the data collected and then drawing conclusions. The results of this study indicate that the professionalism of PAI teachers at Madrasah Aliyah Nurul Islam Jati Agung, South Lampung can be seen from their ability to carry out their professional duties, which include personality competence, social competence, and professional competence. In the teaching and learning process, PAI teachers teach subjects that are in accordance with the basic education and science they are learning, so that teachers are able to plan, implement and evaluate the teaching and learning process properly, although there are still some teachers who have educational backgrounds not from the field or department of teacher training. In terms of performance, PAI teachers at Madrasah Aliyah Nurul Islam Jati Agung, South Lampung in carrying out their duties have high commitment and loyalty and are based on dedication, besides that teachers are disciplined and able to work together with all school members to implement school programs in order to improve student learning achievement of PAI teachers at Madrasah Aliyah Nurul Islam Jati Agung, South Lampung.